Blood immune profiling of Ethiopian patients with breast cancer highlights different forms of immune escape - Meron Yohannes; Chiara Massa; Zelalem Desalegn; Kathrin Stückrath; Anja Mueller; Endale Anberber; Yonas Bekuretsion; Mathewos Assefa; Pablo Santos; Adamu Addissie; Marcus Bauer; Claudia Wickenhauser; et al. (OncoImmunology)
Breast cancer (BC) is a leading cause of death worldwide, particularly also among African woman. In order to better stratify patients for the most effective (immuno-) therapy, an in depth characterization of the immune status of BC patients is required. In this study, a cohort of 65 Ethiopian patients with primary BC underwent immune profiling by multicolor flow cytometry on peripheral blood samples collected prior to surgery and to any other therapy. Comparison with peripheral blood samples from healthy donors highlighted a general activation of the immune system, accompanied by the presence of exhausted CD4+ T cells and senescent CD8+ T cells with an inverted CD4/CD8 ratio in approximately 50% of BC cases. Enhanced frequencies of γδ T cells, myeloid-derived suppressor cells and regulatory T cells were also found. Correlation with clinical parameters demonstrated a progressive reduction in T cell frequencies with increasing histopathological grading of the tumor. Differences in CD8+ T cells and B cells were also noted among luminal and non-luminal BC subtypes. In conclusion, Ethiopian BC patients showed several alterations in the composition and activation status of the blood immune cell repertoire, which were phenotypically associated with immune suppression. The role of these immunological changes in the clinical outcome of patients with BC will have to be determined in follow-up studies and confirmed in additional patients’ cohorts.